KURIKULUM PENDIDIKAN PANTI ASUHAN: Analisis Sistem Kurikulum Pendidikan di Panti Asuhan Bismar Al-Mustaqim Surabaya - Ridwan, Ira Putri Amalia; Handayaningrum, Warih; Yanuartuti, Setyo (Jurnal Empowerment, 2025)
LKSA Bismar Al-Mustaqim Orphanage implements a curriculum based on the salaf pesantren education system to build the foundation of faith and character of foster children. The curriculum consists of three levels according to age and the level of complexity of learning: basic for teaching the Qur'an, intermediate for the introduction of Arabic and yellow book studies in bandongan, and advanced for individual deepening of knowledge through the sorogan method. In addition to religious-based education, the orphanage also applies semi-authoritarian and democratic parenting using exemplary methods, habituation, dialogue, and counseling guidance. Despite facing internal obstacles such as caregiver fatigue, the diversity of children's characters, and external challenges in the form of economic dependence on donors, the orphanage still shows a significant positive impact. This can be seen from the various awards achieved, reflecting the orphanage's commitment in producing a generation with character and virtue